Extensive intracranial involvement with multiple dissections in a case of giant cell arteritis - Parra, J (2014)
A 56-year-old man presented with weight loss, articular pain and minor neurological symptoms progressing over 1 month. Neurosonological evaluation suggested occlusion in intracranial segments of the left vertebral artery (VA) and of both internal carotid arteries (ICA) and hypoechoic halo sign in both superficial temporal arteries. The diagnosis of giant cell arteritis was supported by inflammatory markers and confirmed by biopsy. Despite early steroid initiation, he manifested fluctuant vascular deficits and became lethargic. Brain MRI indicated watershed infarcts and intracranial dissections of left VA and both ICA. The patient was stabilised with the association of prednisolone 2 mg/kg, methotrexate and oral anticoagulation. Since then he has been neurologically asymptomatic and control imaging showed only residual intracranial left VA stenosis, with no signs of temporal artery inflammation or new vascular lesions. This is to the best of our knowledge, the first reported clinical case with such an extensive intracranial involvement with multiple dissections.